M1-like monocytes are a major immunological determinant of severity in previously healthy adults with life-threatening influenza. - Cole, S; Dunning, J; Kok, W; Benam, K; Benlahrech, A; Repapi, E; Martinez, F; Drumright, L; Powell, T; Bennett, M; Elderfield, R; Thomas, C; et al. (American Society for Clinical Investigation, 2017)
In each influenza season, a distinct group of young, otherwise healthy individuals with no risk factors succumbs to life-threatening infection. To better understand the cause for this, we analyzed a broad range of immune responses in blood from a unique cohort of patients, comprising previously healthy individuals hospitalized with and without respiratory failure during one influenza season, and infected with one specific influenza A strain. This analysis was compared with similarly hospitalized influenza patients with known risk factors (total of n = 60 patients recruited). We found a sustained increase in a specific subset of proinflammatory monocytes, with high TNF-α expression and an M1-like phenotype (independent of viral titers), in these previously healthy patients with severe disease. The relationship between M1-like monocytes and immunopathology was strengthened using murine models of influenza, in which severe infection generated using different models (including the high-pathogenicity H5N1 strain) was also accompanied by high levels of circulating M1-like monocytes. Additionally, a raised M1/M2 macrophage ratio in the lungs was observed. These studies identify a specific subtype of monocytes as a modifiable immunological determinant of disease severity in this subgroup of severely ill, previously healthy patients, offering potential novel therapeutic avenues.